Produktivitas Getah Pinus (Pinus Merkusii Jungh Et De Vriese) Berdasarkan Ketinggian Tempat dan Konsentrasi Stimulansia Asam Cuka (C2H4O2) - Arvand Samosir; Ridwanti Batubara; Afifuddin Dalimunthe (Program studi Kehutanan USU, 2015)
The Production of oleoresin is affected by the application of stimulant and effect of elevation. The purpose of this research were to know the effect of C2H4O2 stimulant and effect of elevation to P. merkusii and to know the C2H4O2 concentration and the best of elevation. This research were carried at working area of PT. Inhutani IV, Siborong-borong in March – April 2014 using factorial randomized block design with two factors, i.e. the concentration of stimulant (0, 10, 20 and 30%) and elevation (900 m, 1050-1150 m, 1150-1250 m, 1250-1350 m and 1350-1400 m). Parameter measured were quality and quantity of oleoresin (gram). Result of this research showed that the application of C2H4O2 stimulant on the tapping of pine trees increase considerably to oleoresin. The concentration of C2H4O2 (30%) and the elevation 900 meters can gave the best product of oleoresin, i.e. 154,15 grams/tree/month. Quality of oleoresin were got at this research was B quality.Key word : P. merkusii, resin, stimulant, elevation.